A Qualitative Case Study on The Formation of High Self-Esteem in Visually Impaired Adolescents Based on Coopersmith’s Theory - Agustina, Karina; Sulastri, Sulastri; Syah, Tansri Adzlan (Altruistik : Jurnal Konseling dan Psikologi Pendidikan, 2025)
This study explores the process of developing high self-esteem among visually impaired adolescents at SLB A Bina Insani, Bandar Lampung, based on Coopersmith's Self-Esteem Theory (1967). A qualitative approach with a multiple case study design was used to explore in depth the psychological and social processes underlying self-esteem. Three participants with high self-esteem were selected using the Coopersmith Self-Esteem Inventory (CSEI). Data were collected through in-depth interviews, observations, and documentation, then analyzed thematically. The results show that high self-esteem is formed dynamically through the interaction of internal and external factors. Coopersmith's four factors : acceptance, control, expectations and standards, and rewarding of competence interact with aspects of self-esteem : significance, competence, virtue, and power through self-acceptance, realistic expectations, independence, and appreciation of self-competence. Social support from family, teachers, and peers strengthens this process, resulting in independence, optimism, and resilience in the face of stigma and obstacles. This study emphasizes the importance of unconditional acceptance from family, an inclusive and supportive learning environment, and a culture of appreciation to support the development of positive self-esteem in visually impaired adolescents